Review on Gallium in Coal and Coal Waste Materials: Exploring Strategies for Hydrometallurgical Metal Recovery - Ewa Rudnik (Molecules)
Gallium, a critical and strategic material for advanced technologies, is anomalously enriched in certain coal deposits and coal by-products. Recovering gallium from solid residues generated during coal production and utilization can yield economic benefits and positive environmental gains through more efficient waste processing. This systematic literature review focuses on gallium concentrations in coal and its combustion or gasification by-products, modes of occurrence, gallium-hosting phases, and hydrometallurgical recovery methods, including pretreatment procedures that facilitate metal release from inert aluminosilicate minerals. Coal gangue, and especially fly ashes from coal combustion and gasification, are particularly promising due to their higher gallium content and recovery rates, which can exceed 90% under optimal conditions. However, the low concentrations of gallium and the high levels of impurities in the leachates require innovative and selective separation techniques, primarily involving ion exchange and adsorption. The scientific literature review revealed that coal, bottom ash, and coarse slag have not yet been evaluated for gallium recovery, even though the wastes can contain higher gallium levels than the original material.